2015
DOI: 10.1134/s0006297915010071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trehalose on oxygen evolution and electron transfer in photosystem 2 complexes

Abstract: The pigment-protein complex of photosystem 2 (PS 2) catalyzes the light-driven oxidation of water molecule and the reduction of plastoquinone. In this work, we studied the effect of the disaccharide trehalose, which is unique in its physicochemical properties, on isolated PS 2 complex. It was found that trehalose significantly stimulated the steady-state rate of oxygen evolution. The study of single flash-induced fluorescence decay kinetics demonstrated that trehalose did not affect the rate of QA(-) oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It was reported that PsbP, one of the extrinsic OEC proteins, is essential for the normal PSII function in higher plants in vivo (Ifuku et al 2005), and it plays an important role in the dynamic life cycle of PSII (Ifuku et al 2008, Ifuku et al 2011. In this way, the upregulation of the PsbP content in the Tre-treated group during the recovery period helps to the recovery of PSII, which is in agreement with the result reported by Mamedov et al (2015) that trehalose significantly stimulates the steady-state rate of O2 . Effects of exogenously supplied trehalose and heat stress on protein levels in wheat control seedlings (CK) and plants that pretreated with trehalose for 3 d (Tre).…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that PsbP, one of the extrinsic OEC proteins, is essential for the normal PSII function in higher plants in vivo (Ifuku et al 2005), and it plays an important role in the dynamic life cycle of PSII (Ifuku et al 2008, Ifuku et al 2011. In this way, the upregulation of the PsbP content in the Tre-treated group during the recovery period helps to the recovery of PSII, which is in agreement with the result reported by Mamedov et al (2015) that trehalose significantly stimulates the steady-state rate of O2 . Effects of exogenously supplied trehalose and heat stress on protein levels in wheat control seedlings (CK) and plants that pretreated with trehalose for 3 d (Tre).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, trehalose significantly stimulates and stabilizes the oxygen evolution rate in the PSII complex (Mamedov et al . 2015). Our results indicate that the trehalose pretreatment increased the PQ pool under the heat and drought stresses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose also significantly stimulates the stabilized oxygen evolution rate in the PSII complex (Mamedov et al . 2015). However, the specific protective mechanism of trehalose against stresses remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the content of β-antiparallel content might be caused by increased polymerization. Trehalose can influence the hydration degree of proteins, causing them to adopt a more optimal conformation (Mamedov et al 2015). Under heat stress, protein secondary structures in trehalosepretreated seedlings remained relatively stable, especially ordered α-helix content, which was observably higher than in the control (Table 1).…”
Section: O N L I N E F I R S Tmentioning
confidence: 98%